Efficient rotational cooling of Coulomb-crystallized molecular ions by a helium buffer gas - Hansen, Anders Kragh; Versolato, O. O.; Kłosowski, Ł; Kristensen, S. B.; Gingell, A.; Schwarz, M.; Windberger, Alexander; Ullrich, J.; Crespo López-Urrutia, José Ramon; Drewsen, M. (Nature, 2014)
In combination with sympathetic cooling of translational degrees of freedom (leading to Coulomb crystallization), cooling of the rotational degrees of freedom of magnesium hydride ions using a helium buffer gas leads to temperatures in a tunable range from 60 kelvin down to about 7 kelvin for a single ion, the lowest such temperature so far recorded.
Gesehen am 29.06.2021